Comparative assessment of saliva and plasma for drug bioavailability and bioequivalence studies in humans - Nasir M. Idkaidek (Elsevier, 2017)
Aims: To study the pharmacokinetics of selected drugs in plasma and saliva matrixes in healthy human volunteers, and to suggest using non-invasive saliva sampling instead of plasma as a surrogate in bioavailability and bioequivalence (BA/BE) studies. Methods: Four different pilot BA/BE studies were done in 12-18 healthy humans. Saliva and plasma samples were collected for 3-5 half life values of metformin, tolterodine, rosuvastatin, and paracetamol after oral dosing. Saliva and plasma samples were assayed using LC-MSMS, and then pharmacokinetic parameters were calculated by non-compartmental analysis using Kinetica program. Effective intestinal permeability (Peff) values were also optimized to predict the actual average plasma profile of each drug by Nelder-Mead algorithm of the Parameter Estimation module using SimCYP program. Results: All studied drugs showed salivary excretion with strong correlation coefficients between saliva and plasma concentrations. The optimized Peff ranged 1.44-68.3 × 10−4 cm/s for the drugs under investigation. Saliva/plasma concentrations ratios ranged 0.17-1.5. Inter and intra individual variability of primary pharmacokinetic parameters in saliva matrix was either close to or higher than plasma matrix. This requires larger sample size in saliva studies for some drugs. Conclusion: Our results suggest that there is a potential in BA/BE studies for saliva to be considered as a surrogate for plasma concentration, which goes along with drug regulations. The use of saliva instead of plasma in such studies makes them non-invasive, easy and with a lower clinical burden.